PERAN KONSULTAN MANAJEMEN KONSTRUKSI DALAM OPTIMALISASI REGULASI SLF (Studi Kasus Gedung Terpadu dan Gedung Kuliah Fisipol Kampus Sidotopo Universitas Tidar Magelang) - Gunawan, Wawan; Antonius, Antonius; Wibowo , Kartono (Jurnal Teknik Sipil dan Arsitektur, 2026)
The issuance of the Certificate of Proper Function (SLF) constitutes the final stage in ensuring that a building complies with safety, health, comfort, and accessibility (K4) requirements, as mandated by Government Regulation No. 16 of 2021. This study analyzes the role of the Construction Management Consultant (CMC) in optimizing regulatory compliance for SLF in the Integrated Lecture Building and Fisipol Building Project at Universitas Tidar Magelang. A descriptive qualitative method with a case study approach was employed, involving interviews, field observations, and document reviews. Data were analyzed using the interactive model of Miles & Huberman. The findings reveal that the CMC plays a crucial role in enhancing SLF compliance through three primary functions: (1) Preventive auditing of the Detailed Engineering Design (DED), which identified design discrepancies and potential risks; (2) Quality Assurance and Quality Control (QA/QC) based on SNI 2847:2019 and SNI 1726:2019 to ensure construction accuracy; and (3) Functional system verification, including assessment of MEP and fire protection systems through installation evaluation and commissioning tests. These optimized functions significantly improved project compliance with SLF requirements and minimized legal risks. The study recommends the development of internal operational standards and the adoption of BIM to strengthen documentation and streamline SLF regulatory verification. Keyword: Construction Management Consultant, SLF, Regulatory Compliance, Preventive Audit, QA/QC, SNI Standards.